Pengaruh Struktur Modal, Ukuran Perusahaan, Inflasi, dan Suku Bunga terhadap Kinerja Keuangan Perusahaan: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI - Nurul Hidayah; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2026)
Inflation, interest rates, firm size, and capital structure are the variables that this research intends to analyze. Quantitative research with an emphasis on causation characterizes this investigation. Companies listed on the Indonesia Stock Exchange (IDX) in the manufacturing Industry during 2021–2023 make up the population of this study. A purposive sampling technique was used to determine the sample, and 75 companies were obtained as samples. Multiple regression analysis in SPSS 20 was the statistical method employed in this research. Return on Assets (ROA) is a metric used to calculate financial performance. To account for the present macroeconomic dynamics, this study adds something new by substituting inflation and interest rates for liquidity and sales growth, two variables that have been utilized in earlier research. Results from this study's simultaneous testing demonstrate that independent variables have an effect on the dependent variable at the same time. Having said that, there is a partial positive impact on financial performance from two of the four independent variable measurements capital structure and company size and a partial negative effect from inflation and interest rate variables.